2023
DOI: 10.1002/rnc.6672
|View full text |Cite
|
Sign up to set email alerts
|

Event‐triggered adaptive control of strict‐feedback nonlinear systems under output constraints and unknown control direction

Abstract: This article is concerned with the tracking control problem for a class of uncertain nonlinear systems under output constraints and unknown control direction. To address the unknown control direction and uncertain system parameters, the adaptive compensation mechanism and Nussbaum gain based control technique are employed. In addition, to reduce the communication burden and computing cost, the event‐triggered control mechanism is introduced into the proposed control scheme, in which both the controller and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…This strategy is based on periodically sampled signals, hence it can avoid the Zeno phenomenon in mechanism, moreover, it has been shown that it can further reduce the communication frequency compared with the continuous strategy. From another point of view, ETC strategies can be classified as the static ETC (SETC) strategy [2][3][4][5] and the dynamic ETC (DETC) strategy [6][7][8][9]. In the SETC strategy, the triggering instants are determined by a static trigger function depending on the current state signal and the last transmitted one.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy is based on periodically sampled signals, hence it can avoid the Zeno phenomenon in mechanism, moreover, it has been shown that it can further reduce the communication frequency compared with the continuous strategy. From another point of view, ETC strategies can be classified as the static ETC (SETC) strategy [2][3][4][5] and the dynamic ETC (DETC) strategy [6][7][8][9]. In the SETC strategy, the triggering instants are determined by a static trigger function depending on the current state signal and the last transmitted one.…”
Section: Introductionmentioning
confidence: 99%
“…An event‐triggered communication or transmission mechanism has been proposed to save resources, such as References 10,11. Compared with conventional time‐triggered control, event‐triggered control (ETC) offers efficiencies in communication as the updating of control only occurs when the system needs it while retaining the required closed‐loop performance 12,13 . The first important issue with ETC is ensuring that the minimum inter‐event time (the minimum time interval between two consecutive events) is more significant than some normal number.…”
Section: Introductionmentioning
confidence: 99%